Karya Musik Dialog Sonic: Kolaborasi Saxophone, Gitar, Kecapi, Dan Tabla - Ramadan, Raden Irfansyah (CV. ITTC INDONESIA, 2025)
This artistic practice-based research aims to create a collaborative musical work as a sonic dialogue between Western and Eastern music. The instruments utilized include saxophone and guitar, representing Western idioms, and kacapi (Sundanese) and tabla (Indian), representing Eastern traditions. The creation process involved three main stages: idiom exploration, improvisational experimentation, and final composition arrangement. The findings demonstrate the feasibility of integrating rhythmic structures (tala) and traditional melodic patterns (pelog/salendro) with modern jazz harmony and improvisation. The collaborative process fostered active dialogue among musicians from diverse cultural backgrounds, inherently cultivating cross-traditional understanding. Analysis of the work confirms that idiomatic synthesis is achievable without compromising each instrument's musical identity, provided there is aesthetic, technical, and cultural awareness throughout the creation stages. This work not only yields new musical forms but also underscores the significance of an intercultural approach in contemporary art. Furthermore, the creative process serves as a reflective vehicle for re-evaluating the relationship between individual expression, cultural identity, and the potential for equality in cross-traditional collaboration